2021
DOI: 10.1002/aic.17137
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of methyl iodide on reduced silver‐functionalized silica aerogel: Kinetics and modeling

Abstract: The low concentration methyl iodide (CH3I) adsorption process on reduced silver‐functionalized silica aerogel (Ag0‐Aerogel) was studied. The kinetic data were acquired using a continuous flow adsorption system. Because the corresponding physical process was observed, the shrinking core model (SCM) was modified and applied. An average CH3I pore diffusivity was calculated, the CH3I‐Ag0‐Aerogel reaction was identified as a 1.40 order reaction instead of first order reaction, and the nth order reaction rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…19−22 Ag 0aerogel is a relatively new material developed at Pacific Northwest National Laboratory (PNNL), and its high Ag content and adequate specific surface area aid in iodine capture, making it an appealing alternative to zeolites that have traditionally been the primary focus in this area. 23,24 By exposing Ag 0 Z and Ag 0 -aerogel to gas streams containing the aforementioned off-gas components at 150 °C, we found that NO 2 significantly reduced the I 2 capacity for both materials (∼90% reduction after 1 month), 21,22 while O 2 , H 2 O, and NO were less impactful (30%−80% reduction for Ag 0 Z and ∼20% reduction for Ag 0 -aerogel after 1 month). 19,20 Though the existence of the aging phenomenon is well established, there are still, nevertheless, some discrepancies that arise when attempting to understand its underlying processes.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…19−22 Ag 0aerogel is a relatively new material developed at Pacific Northwest National Laboratory (PNNL), and its high Ag content and adequate specific surface area aid in iodine capture, making it an appealing alternative to zeolites that have traditionally been the primary focus in this area. 23,24 By exposing Ag 0 Z and Ag 0 -aerogel to gas streams containing the aforementioned off-gas components at 150 °C, we found that NO 2 significantly reduced the I 2 capacity for both materials (∼90% reduction after 1 month), 21,22 while O 2 , H 2 O, and NO were less impactful (30%−80% reduction for Ag 0 Z and ∼20% reduction for Ag 0 -aerogel after 1 month). 19,20 Though the existence of the aging phenomenon is well established, there are still, nevertheless, some discrepancies that arise when attempting to understand its underlying processes.…”
Section: Introductionmentioning
confidence: 89%
“…Nevertheless, the uptake rate is much higher in powdered Ag 0 -aerogel and Ag 0 Z since the pellet samples exhibit a distinct shrinking-core process where the adsorption rate is transport limited. 24,26 The I 2 uptake rate for Ag S is the second slowest of the five samples tested with the slowest being the Ag 0 Z pellet, and it takes much longer for Ag 2 S to reach equilibrium (i.e., maximum amount of Ag was converted to AgI). Since the Ag content determines the maximum I 2 capacity, a better approach to evaluate the uptake kinetics is to compare the Ag utilization rate of the different samples.…”
Section: Examination Of Ag 2 S As An Adsorbent For Imentioning
confidence: 99%
See 1 more Smart Citation
“… Summary of various parameters for consideration when selecting sorbents for radioiodine: (A) optimal capture performance including different types of Ag-zeolites that have different Ag loadings ( Riley et al, 2022b ) (criterion-1), (B) sorbent kinetics including examples based off actual data for I 2 ( Riley et al, 2014 ) for sulfide-based chalcogels and CH 3 I for Ag 0 -aerogels ( Tang et al, 2021 ) [in parts per billion by volume (ppbv) CH 3 I concentration streams] (criterion-2), (C) performance under relevant conditions based off data for I/Cl coadsorption ( Matyáš et al, 2021b ) and other studies in this area ( Riley et al, 2021 ; Riley et al, 2022a ) (criterion-3), (D) inherent properties of sorbent substrate ( Riley et al, 2021 ) (criterion-4), and (E) iodide stability and disposition pathways ( Riley et al, 2021 ; Reiser et al, 2022 ) (criterion-5). …”
Section: Introductionmentioning
confidence: 99%
“…4−6 Among them, 129 I has raised many concerns due to its very long half-life (1.7 × 10 7 years). 7,8 The main methods of capturing radioactive iodine in exhaust gas include liquid and solid material adsorption. 9 Silver-loaded solid adsorbents, especially silver-loaded silica gel (AgS), are widely used in the industrial treatment of radioactive iodine, owing to their excellent adsorption capacity and easy assembly.…”
Section: Introductionmentioning
confidence: 99%